Climatic influences on the variations of wet paddy (Oryzae sativa L)yields in the various states of Peninsular Malaysia - Ong , Hean Tatt (1983)
The wet paddy yields in the states of Peninsular Malaysia during the 1975/76 main and 1976 otf seasons were studied in relation to changes in rainfall, dry spells, sunshine, maximum and minimum temperatures through the principles of system approach. The main climatic factors influencing the yields were identified as rainfall during the 2nd to 5th months before harvest, the mean minimum temperature of the 4th month before harvest and the mean maximum temperature of the month before harvest, accounting for 83.92% of the variations in the wet paddy yields. The various states of Peninsular Malaysia had consisten t differences in wet paddy yields since 1946 to through 1977 and these regional differences in yields appeared principally due to the climatic changes in rainfall and air temperatures.